Crossover Design on the Bioequivalence of Pharmaceuticals - A Case of Study - M. Filomena Teodoro; Andrade, M. A. P.; Oliveira, A. (The 24th International Conference on Computational Science and Its Applications (ICCSA 2024), 2024)
This study performs experimental design and analysis of variance in assessing the bioequivalence of two treatments, which involves evaluating the efficacy of different treatments administered to two distinct cohorts of patients: the control group and the test group. In order to compare the control group that received the reference medication, with the test/treatment group that received the investigational drug, a crossover experimental design was employed. The respective analysis of variance was conducted, taking into consideration both intra-subject and inter-subject variability in formulating the probabilistic model. This included specifying tests to detect carryover effects and period effects. The practical implementation of the proposed model involved validating the hypothesis, revealing that the carry-over effect was found to be not significant, when assessed at the usual levels of significance (1% and 5%). In terms of the treatments, it was concluded that there was statistical significance, leading to the assertion that the studied pharmaceuticals were not bioequivalent.